The influence of sense of coherence on psychological birth trauma: a parallel mediation model based on health Salutogenesis theory - Zeng, Tieying; Jiang, Lingjun; Zhang, Ke; Wu, Meiliyang; Zhu, Zining; Hu, Zhenjing (Frontiers in Psychology, 2024)
Background: Psychological birth trauma has been associated with a variety of negative consequences for mothers, partners, newborns, and midwives. While prior research has identified demographic and clinical factors that may contribute to the development of psychological birth trauma, interventions targeting these factors can prove challenging. Therefore, the aim of this study was to explore how psychological birth trauma is influenced by psychosocial factors including Sense of Coherence, Childbirth-related Fear, Social Support and Childbirth Readiness.A cross-sectional study was conducted in 13 tertiary or secondary hospitals in mainland China from November 2021 to June 2022. 1366 women were recruited totally. Data regarding basic characteristics, Sense of Coherence (SOC, Sense of Coherence Scale-3), Childbirth-related Fear (CBRF, Fear of Childbirth Scale), Social Support (SS, Medical Outcomes Study Social Support Survey), Childbirth Readiness (CR, Childbirth Readiness Scale) and Psychological Birth Trauma (PBT, Psychological Birth Trauma Scale) were collected. Parallel mediation analysis was adopted to identify the underlying mechanisms between study variables.Results: It was found that: (1) SOC has been found to have both direct and indirect effects on PBT. Women with higher level of SOC tend to report lower level of PBT; (2) the indirect effect of SOC on PBT was significantly exerted through CBRF, SS and CR; (3) CBRF was found to weaken the protective effect of SOC, whereas SS and CR were found to enhance it. No significant difference was found in contracts of the three specific indirect effects.Conclusion: SOC, CBRF, SS and CR should be paid enough attention when designing intervention programs for women who might experience PBT. Interventions targeting SOC and CR are more likely to yield positive outcomes.